Instandsetzung einer maroden Verkehrsinfrastruktur – Ursachen, Herausforderungen und Lösungen - Gernot Sieg (Wirtschaftsdienst, 2025)
– Germany established a exteuro300 billion special fund to upgrade its decaying infrastructure and reach climate neutrality by 2045. However, funding gaps, governance issues and inefficiencies persist, especially in rail, road, and waterway networks. Structural reforms, such as the creation of DB InfraGO and Autobahn GmbH, failed to align objectives with financing. The flat-rate Germany Ticket faces legal and economic challenges. Effective climate policy and emissions trading are hindered by political compromises. A governance overhaul is needed to ensure sustainable, efficient infrastructure investment and management.
Keywords: H54; L91; Q58; 330